PANDANGAN MUI PROVINSI SUMATERA SELATAN TERHADAP PENYALURAN DANA ZAKAT DI BAZNAS PROVINSI SUMATERA SELATAN BAGI YANG SEDANG MENUNTUT ILMU - Fatima, Dewi; Atika, Atika; Sunaryo, Yono (Program Studi Muamalah Fakultas Syariah dan Hukum, 2018)
ABSTRAC Management of the Amil Zakat Agency is an activity of planning, organizing, implementing and supervising the collection and distribution and utilization of zakat formed by the government to increase the benefits of zakat to realize community welfare and poverty reduction. With the lively education there are many scholarships offered from various agencies, especially in BAZNAS itself, and with the assistance of BAZNAS for those who are studying there is no reason not to continue their education if it is really intended to go to school. Thus the authors are interested in discussing the views of the MUI of South Sumatra Province on the Distribution of Zakat Funds at the National Bureau of Religion in South Sumatra Province for those who are demanding knowledge. The problems raised in the writing of this Thesis are how the forms of zakat fund distribution in BAZNAS of South Sumatra Province for those who are studying and how the views of the MUI of South Sumatra Province on the forms of zakat funding in BAZNAS of South Sumatra Province for those who are studying. The method used in this study uses the field (Research Fiel), literature study (library research), and documentation studies. The data sources used are primary and secondary. Primary legal material is the main data source consisting of data relating to the distribution of zakat funds obtained at BAZNAS and MUI directly related to the object of research. Secondary legal material is a data source that provides an explanation of primary data consisting of books and research results related to the distribution of zakat funds. The data collected in this study was then analyzed descriptively qualitatively, which explained all the data in the subject matter clearly and clearly. Then the explanation is deductively concluded that is drawing a conclusion. from general statements to specific statements, so that the final presentation of this research can be easily understood. From the results of the research obtained, the authors conclude that the distribution of zakat funds in BAZNAS of South Sumatra Province has been fulfilled with their respective needs but only concentrated in two education, namely South Sumatra Smart which has 3 program stages, namely: first SKSS, second Bina Santri, third Direct proposal. Then according to MUI (Indonesian Ulema Council) of South Sumatra Province the distribution of zakat funds for those who demand knowledge is valid by considering: Academic achievement, prioritized for those who are less fortunate, and learning knowledge that is beneficial for the Indonesian people. Keywords: Distribution, Zakat, Fii Sabilillah.